Respuesta :
Answer:
7x-20=2x-3(3x+2)
We move all terms to the left:
7x-20-(2x-3(3x+2))=0
We calculate terms in parentheses: -(2x-3(3x+2)), so:
2x-3(3x+2)
We multiply parentheses
2x-9x-6
We add all the numbers together, and all the variables
-7x-6
Back to the equation:
-(-7x-6)
We get rid of parentheses
7x+7x+6-20=0
We add all the numbers together, and all the variables
14x-14=0
We move all terms containing x to the left, all other terms to the right
14x=14
x=14/14
x=1
Step-by-step explanation:
Answer:
x = 1
Step-by-step explanation:
7x - 20 = 2x - 3(3x + 2)
7x - 20 = 2x - 9x - 6
7x - 2x + 9x = - 6 + 20
14x = 14
x = 14/14
x = 1